Las empresas ferroviarias en las provincias de Entre Ríos, Corrientes y Misiones (1866-2014). Entre intereses globales, nacionales y regionales - Rascovan, Alejandro (2015)
The construction of railways in the provinces of Entre Rios and Corrientes began in the 1860’s decade. Private investors, mainly from England and France, allied with national and provincial governments, developed a wide network of standard gauge railways (1.435mm) that enabled the linkage between those territories and Buenos Aires and boosted the demographical and economic progress. In the 1940’s decade, the international bridge with Brazil was opened, joining for the first and yet only time both railway networks, opening new regional perspectives. After the nationalization, in 1947, the railways entered a time of crisis, which permitted the neoliberal governments to re-privatize the public companies. Under the control of the brazilian America Latina Logistica, the railways had to adapt to a the new regional integration logics in a context where railway transportation faces an identity crisis